Resonanzfähigkeit: resonance capability in Luhmannian systems theory. Issue 10 (2nd December 2019) - Clark, Carlton
Abstract : Purpose: This paper aims to contribute to the sociological literature on moral communication and disciplinary apparatuses in a functionally differentiated society. It combines Luhmannian and Foucauldian theories to further the understanding of social system complexity. Design/methodology/approach: The paper draws on the work of Niklas Luhmann, Michel Foucault and others to explore resonance capability, disciplinary apparatuses and the complexity–sustainability trade-off. The argument is illustrated with a discussion of the late-nineteenth- to early-twentieth-century anti-child labor movement. Findings: The paper argues that organizations are better equipped than function systems to draw moral distinctions. Given the amorality of the function systems and the increasing secularization of modern society, a great deal of moral communication now occurs in non-religious organizations. These social systems increase their complexity in response to new problems, but the increased system complexity may become unsustainable. Research limitations/implications: The paper contributes to the growing sociological literature that compares and sometimes attempts to synthesize the theories of Luhmann and Foucault. It also contributes to the literature on organizational theory. Originality/value: The paper brings together the work of Luhmann, Foucault, Valentinov and others to advance the understanding of organizations and moral communication in a functionally differentiated society. It uses Google Books Ngrams, among other resources, to support the argument.